Hedgehug's Halloween - Sutton, Benn (Harper, an imprint of HarperCollins Publishers, 2013)
Hoping to attend the biggest Halloween party of the year in just a few hours, Hedgehug tries to put together the perfect costume with the help of his friends but fears he will not be ready in time.